Analisis Pengaruh Kualitas Produk, Kualitas Layanan dan Keragaman Produk Terhadap Kepuasan Pelanggan Serta Dampaknya Terhadap Minat Beli Ulang (Studi pada Toko Online Shopastelle, Semarang) - Arsyanti, Nuri Mahdi; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2016)
This study was conducted at online store called Shopastelle, which is located in Semarang. The purpose of this study is to analyze the effect of product quality, quality of service, price and customer satisfaction as well as the impact on repurchase intention.The population used in this study are customers who've bought the Shopastelle product. By testing the 100 respondents, this study uses five variables, 22 indicators and four hypotheses. Methods of data analysis used in this study the methods of quantitative analysis using multiple linear regression analysis. The results showed that the product quality has a positive influence on customer satisfaction; quality of service has a positive influence on customer satisfaction; product diversity has a positive influence on customer satisfaction; and customer satisfaction has a positive influence on repurchase intention.